Yield and Its Components of Shallot (Allium ascalonicum L.) Influenced by the Application of Amino Acid Fertilizer And Triacontanol - Putra, Anggara Ista; Waluyo, Budi; Nihayati, Ellis (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2022)
Shallot are one of the agricultural products with a relatively high demand for the consumer market in Indonesia, but the productivity figure is relatively low compared to other countries (FAO, 2021). This study seeks to explore the effectiveness of the application of amino acid fertilizer and triacontanol in increasing the yield and yield components of shallot. The study was conducted in Karangploso District, Malang, from April to August 2021. In a randomized block design, this study used two factors: amino acid fertilizers (A1: 1 g plot-1; A2: g plot-1; A3: 5 g plot-1) and triacontanol (T0: 0 ppm; T1: 5ppm; T2: 10 ppm). Each combination was repeated three times. As a result, amino acid fertilizers can significantly affect the number of shallot bulbs, yields per hectare, economic weight, and economical weight loss. A significant effect was seen in the application of triacontanol on shallot yields per hectare and economic weight. The interaction of characters of bulb length was shown in the combination of 5-10 ppm triacontanol with amino acid fertilizer. The best response ranged from 10.64% to 11.67% in fertilizer with 5 g plot-1 of an amino acid fertilizer. As the doses of amino acid fertilizer in combination with triacontanol increased, the total bulb fresh weight grew as well, in which 5 g plot-1 of amino acid fertilizer could increase the weight by 45,23-45,43 g clump-1, which was greater than the response of the 1 g plot-1 amino acid fertilizer combination.